ANALISIS KUANTITATIF ISOFLAVON TEMPE SECARA CEPAT DAN SEDERHANA MENGGUNAKAN METODE KROMATOGRAFI LAPIS TIPIS- DENSITOMETRI - Agustina Setiawati; Sri Hartati Yuliani; Enade Perdana Istyastono; Evy Fenny Veronica; Dina Christin Ayuning Putri; Reza Eka Putra; David Chandra Putra; Agnes Mutiara Kurniawan; Michael Raharja Gani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Rapid and simple quantitative analysis isoflavones tempe using densitometric TLChas been done. The mobile phase of the system was chloroform: methanol: ethylacetate (45: 5:0.75). Thin layer chromatography was performed on aluminium TLC plates.Ascending distanceof 1 ?L sample was performanced 10 cm. Then the plate was scanned at 261 nm. A linearrelationship obtained at 0.08 - 2 ?g/spot with r= 0.9986. The LOD and LOQ of isoflavone were0.014 ?g/spot and 0.048 ?g/spot. Genistein contained in tempe was 0.151 0.005 % b/b.